The Use of Role-Play and Guided Discussion Techniques as Speaking Strategies in Arabic Language Learning at Madrasah Aliyah - Faisal Abdullah; Tantri Hasna Fauziah (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to examine the process of implementing the role-play technique in teaching Arabic speaking skills at Madrasah Aliyah, the use of guided discussion as a strategy for Arabic speaking instruction, the effectiveness of combining role-play and guided discussion in improving students’ Arabic speaking abilities, and the supporting and inhibiting factors that influence the application of both strategies. The research employs a descriptive qualitative approach to illustrate the implementation of role-play and guided discussion techniques in Arabic speaking learning at Madrasah Aliyah. Data were collected through observations, interviews, and documentation, both primary and secondary, to capture student interactions, classroom dynamics, and learners’ responses. Data analysis was conducted using the Miles and Huberman model through data reduction, data display, and conclusion drawing, resulting in a detailed picture of the effectiveness of the two techniques in enhancing students’ fluency, accuracy, and speaking confidence. The findings indicate that role-play and guided discussion techniques are effective in improving the Arabic speaking skills of Madrasah Aliyah students. Role-play fosters a communicative atmosphere and builds speaking confidence, while guided discussion enhances critical thinking and language fluency through two-way interaction. The combination of both techniques is the most effective, as each complements the other. Successful implementation is influenced by student motivation, teacher competence, vocabulary mastery, time allocation, and available facilities. Well-prepared instructional planning and a supportive learning environment are essential to optimize these strategies.